ABCA7 Gene Expression and Genetic Association Study in Schizophrenia - Yamazaki K (Dove Medical Press, 2020)
Kiyohiro Yamazaki,1 Yuta Yoshino,1 Kentaro Kawabe,1 Tomomasa Ibuki,1 Shinichiro Ochi,1 Yoko Mori,1 Yuki Ozaki,1 Shusuke Numata,2 Jun-ichi Iga,1 Tetsuro Ohmori,2 Shu-ichi Ueno1 1Department of Neuropsychiatry, Molecules and Function, Ehime University Graduate School of Medicine, Toon, Ehime 791-0295, Japan; 2Department of Psychiatry, Course of Integrated Brain Sciences, Medical Informatics, Institute of Health Biosciences, the University of Tokushima Graduate School, Tokushima 770-8503, JapanCorrespondence: Jun-ichi IgaDepartment of Neuropsychiatry, Molecules and Function, Ehime University Graduate School of Medicine, Shitsukawa, Toon, Ehime 791-0295, JapanTel +81-89-960-5315Fax +81-89-960-5317Email iga.junichi.it@ehime-u.ac.jpIntroduction: Although ATP-binding cassette sub-family A member 7 gene (ABCA7) is known to be associated with Alzheimer’s disease, the relationship between ABCA7 and schizophrenia has been unknown.Methods: Schizophrenia patients (n = 50; 24 males, 62.1 ± 0.50 years old) and age- and sex-matched healthy controls (n = 50) were recruited for the mRNA analysis. Additionally, a case-control study for the rs3764650 genotypes was performed with 1308 samples (control subjects; n = 527, schizophrenia patients; n = 781). All participants were Japanese, unrelated to each other, and living in the same area.Results: The distributions of the rs3764650 genotypes in schizophrenia patients were not different from that of controls. However, the ABCA7 mRNA expression levels in schizophrenia patients were significantly higher than those in controls by a logistic regression analysis. Additionally, the ABCA7 mRNA expression levels in schizophrenia patients were correlated with the rs3764650 genotypes in a dose-dependent manner.Discussion: The ABCA7 mRNA expression levels in peripheral blood with the rs3764650 genotypes may be related to pathological mechanisms in schizophrenia and may be a biological marker for schizophrenia.Keywords: schizophrenia, ATP-binding cassette sub-family A member 7 gene, single nucleotide polymorphism, rs3764650, mRNA expression